2011
DOI: 10.1128/iai.00057-11
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evaluation of Pseudomonas aeruginosa Biofilm Mediators in a Chronic Infection Model

Abstract: Biofilms contribute to Pseudomonas aeruginosa persistence in a variety of diseases, including cystic fibrosis, burn wounds, and chronic suppurative otitis media. However, few studies have directly addressed P. aeruginosa biofilms in vivo. We used a chinchilla model of otitis media, which has previously been used to study persistent Streptococcus pneumoniae and Haemophilus influenzae infections, to show that structures formed in vivo are biofilms of bacterial and host origin within a matrix that includes Psl, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 53 publications
12
63
0
Order By: Relevance
“…P. aeruginosa with psl and pel genes deleted lost their ability to form biofilms altogether, indicating the importance of these exopolysaccharides in early stages of biofilm formation. These data show that alginate, Psl, Pel, and extracellular DNA interactively contribute to some aspect of P. aeruginosa biofilm architecture (16). The current state of knowledge indicates that Psl and Pel are likely involved with the initial stages of biofilm development (or acute stages of infection), whereas alginate is the "stress" response polysaccharide associated with chronic stages of infection.…”
mentioning
confidence: 79%
“…P. aeruginosa with psl and pel genes deleted lost their ability to form biofilms altogether, indicating the importance of these exopolysaccharides in early stages of biofilm formation. These data show that alginate, Psl, Pel, and extracellular DNA interactively contribute to some aspect of P. aeruginosa biofilm architecture (16). The current state of knowledge indicates that Psl and Pel are likely involved with the initial stages of biofilm development (or acute stages of infection), whereas alginate is the "stress" response polysaccharide associated with chronic stages of infection.…”
mentioning
confidence: 79%
“…Small-colony variants generated in vitro as well as obtained from clinical isolates contained mutations that upregulate the activity of the DGC TpbB (YfiN), suggesting a key role of this enzyme (193,245). The importance of c-di-GMP for enhanced persistence of P. aeruginosa has also been demonstrated in a chinchilla model of middle ear infection (355).…”
Section: Cyclic Di-gmp and Virulencementioning
confidence: 95%
“…For instance, 2-aminoimidazole derivatives targeting QS have been designed and found to disperse established biofilms [40,41]. Proof of concept studies showed that in vivo manipulation of c-di-GMP levels can effectively clear (by decreasing c-di-GMP) or prolong (by increasing c-di-GMP) Pseudomonas aeruginosa infections in murine models [42,43]. Modification of the BdcA protein to enhance its c-di-GMP binding, thus reducing the intracellular c-di-GMP concentration, caused nearly complete removal of biofilms via dispersal in vitro [44].…”
mentioning
confidence: 99%